Ti-rich carboborides in the multi-component high-boron alloy: morphology and elemental distribution - Chabak, Yu.G.; Golinskyi М.А.; Efremenko, V.G.; Halfa, H.; Zurnadzhy V.І.; Efremenko, B.V.; Tsvetkova, E.V.; Dzherenova, A.V. (Physics and Chemistry of Solid State, 2023)
In the article, the characterization of the morphology, chemical composition, and elemental distribution in the Ti-based carboboride M(C,B) in (wt.%) Fe-0.72C-2.75B-5.05W-5.57Mo-10.35Cr-2.60Ti multi-component alloy is fulfilled. The study was performed using optical microscopy, SEM, TEM, and energy-dispersive X-ray spectroscopy. It was found that the carboboride M(C,B) is present in the structure in the form of the equiaxed polygonal particles of a 0.5-7.3 mm mean size. The particles are divided into “duplex” and “uniform” ones. The duplex particles consists of the Ti-rich (75 wt. % Ti) “core” (Ti(C,B)) and the Ti-depleted (47.3 wt. % Ti) “shell” ((Ti,W,Mo,V)(C,B)). The uniform particles are characterized by an even distribution of the elements having a chemical composition close to the “shell”. The ratio of B:C (at. %) is 1:2.5, 1:3.3, and 1:3.2 for the “core”, “shell” and the uniform particle respectively. The chemical formulas of the duplex/uniform M(C,B) inclusions and the mechanism of their formation are proposed.